2013
DOI: 10.1177/1076029613502255
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism and Deep Venous Thrombosis Following Laparoscopic Cholecystectomy

Abstract: There is considerable uncertainty related to the thromboembolic risk after laparoscopic cholecystectomy. Patients with pulmonary embolism (PE), deep venous thrombosis (DVT), or venous thromboembolism (VTE) at hospital discharge following laparoscopic cholecystectomy were identified from the Nationwide Inpatient Sample. From 1998 through 2009, 4 107 430 laparoscopic cholecystectomies were performed. The in-hospital prevalence of PE was 0.15%, DVT was 0.40%, and VTE was 0.53%. The prevalence of PE increased from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…The rates of symptomatic VTE (0.3%) and post‐operative bleeding (2.4%) in our cohort are comparable to international studies 14–23 . Importantly, our findings reflect those seen in patients who have undergone hip arthroplasty and spinal surgery, 11,12 that when compared with early chemoprophylaxis, its post‐operative use is associated with a lower risk of bleeding without compromising protection against thromboembolism.…”
Section: Discussionsupporting
confidence: 83%
“…The rates of symptomatic VTE (0.3%) and post‐operative bleeding (2.4%) in our cohort are comparable to international studies 14–23 . Importantly, our findings reflect those seen in patients who have undergone hip arthroplasty and spinal surgery, 11,12 that when compared with early chemoprophylaxis, its post‐operative use is associated with a lower risk of bleeding without compromising protection against thromboembolism.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, Stein et al reported the prevalence of VTE after laparoscopic cholecystectomy increased from 0.17% in patients aged 21 to 30 years to 0.90% in patients aged 71 to 80 years, similar to our findings [28]. White et al reported a steady increase in the incidence of VTE with increasing age in cholecystectomy [8].…”
Section: Other Literaturesupporting
confidence: 91%
“…It is now widely accepted that surgical patients in moderate to high risk of VTE must be given some sort of thromboprophylaxis (3). For laparoscopic cholecystectomy, however, there has been considerable debate on the severity of risk of thromboembolism and hence the necessity of thromboprophylaxis for this surgi-cal procedure (4)(5)(6)(7)(8). Although there is an advantage of laparoscopic cholecystectomy over an open procedure due to reduced surgical trauma; the pneumoperitoneum and reverse Trendelenburg position during the procedure may theoretically lead to venous stasis in legs (5), which may be speculated to increase the risk for thromboembolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is an advantage of laparoscopic cholecystectomy over an open procedure due to reduced surgical trauma; the pneumoperitoneum and reverse Trendelenburg position during the procedure may theoretically lead to venous stasis in legs (5), which may be speculated to increase the risk for thromboembolic complications. On the other hand, a meta-analysis of 153,832 patients (9) and recent large scale clinical studies revealed rather low rates of complications related to venous thromboembolism after laparoscopic cholecystectomy (4,10). One of these studies reported an increased risk of bleeding complications in patients receiving thromboprophylaxis, further questioning the routine use of antithrombotic medication in patients undergoing laparoscopic cholecystectomy (10).…”
Section: Introductionmentioning
confidence: 99%